Publication of works presented in the 2016 and 2018 editions of the National Student Scientific Event on Internal Medicine -MEDINTÁVILA - Frank Hernández-García; Ibraín Enrique Corrales-Reyes; Enrique Rolando Pérez-García; Juan Antonio Sorí-Peña; Onelis Góngora-Gómez; Christian Richard Mejía (Revista de la Facultad de Medicina, 2021)
Introduction: Much of the research works developed by students and presented in scientific events are not published in scientific journals.